Solid particle solar receivers in the next‐generation concentrated solar power plant. Issue 5 (23rd March 2022) - Nie, Fuliang; Bai, Fengwu; Wang, Zhifeng; Li, Xiaobo; Yang, Ronggui
Abstract: Solid particles are generally considered to be the most suitable heat transfer fluid (HTF) and thermal energy storage (TES) materials for the next‐generation concentrated solar power (CSP) plant. The operating temperature of the solar receiver can be raised to exceed 800°C by the application of appropriate solid particles. In this way, power conversion efficiencies greater than 50% can be achieved with the supercritical carbon dioxide (sCO2 ) Brayton cycle. Solid particle solar receiver (SPSR) is the key equipment to absorb the concentrated solar flux, and its thermal performance is remarkably affected by receiver system designs, particle flow characteristics, and properties of solid particulate materials. This paper provides an in‐depth review of various SPSR technologies, as well as pertinent solid particle selections, optimization of the receiver system structures, particle flow characteristics, and heat transfer characteristics. The technical drawbacks, the large‐scale development prospects, and the potential optimization strategies of the various SPSR designs are highlighted by the comparative analysis of multiple parameters. Abstract : This review summarizes the various solid particle solar receiver technologies that are of great interest to both academia and industry. The relevant solid particle selections, optimization of the receiver system structures, particle flow characteristics, and heat transfer characteristics are discussed. Finally, we conclude the technical drawbacks, the large‐scale development prospects, and the potential optimization strategies of the multiple designs.